2003
DOI: 10.1124/mol.64.2.521
|View full text |Cite
|
Sign up to set email alerts
|

cGMP/Protein Kinase G-Dependent Potentiation of Glutamatergic Transmission Induced by Nitric Oxide in Immature Rat Rostral Ventrolateral Medulla Neurons in Vitro

Abstract: Although both nitric oxide (NO) and glutamate within the rostral ventrolateral medulla (RVLM) are important mediators of the central cardiovascular regulation, little is known about the functional interactions between these two mediators. Herein, we investigated the possible role of NO on the glutamatergic transmission of RVLM neurons. Whole-cell patch-clamp recordings were performed on visualized RVLM neurons in the brainstem slice preparation of rats. We found that bath application of Larginine, the substrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
36
1
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 44 publications
5
36
1
1
Order By: Relevance
“…This is in line with previous reports demonstrating that NO interferes with both glutamatergic (Prast et al, 1998) and GABAergic (Wall, 2003) neurotransmission and influences neurotransmitter release depending on the type of synapse (Meffert et al, 1996;Mironov and Langohr, 2007;Wang et al, 2007). NO increases the release of glutamate by modulating presynaptic N-type Ca 2ϩ channels (Huang et al, 2003) and the release of GABA by an elevation of the intracellular Ca 2ϩ concentration via cyclic adenosine diphosphate ribose/ryanodine-sensitive stores (Wang et al, 2006). The increase in transmitter release might also be related to NO-mediated acceleration of recycling of synaptic vesicles (Micheva et al, 2003).…”
Section: Targets Of Endogenous No In Slice Preparationssupporting
confidence: 81%
“…This is in line with previous reports demonstrating that NO interferes with both glutamatergic (Prast et al, 1998) and GABAergic (Wall, 2003) neurotransmission and influences neurotransmitter release depending on the type of synapse (Meffert et al, 1996;Mironov and Langohr, 2007;Wang et al, 2007). NO increases the release of glutamate by modulating presynaptic N-type Ca 2ϩ channels (Huang et al, 2003) and the release of GABA by an elevation of the intracellular Ca 2ϩ concentration via cyclic adenosine diphosphate ribose/ryanodine-sensitive stores (Wang et al, 2006). The increase in transmitter release might also be related to NO-mediated acceleration of recycling of synaptic vesicles (Micheva et al, 2003).…”
Section: Targets Of Endogenous No In Slice Preparationssupporting
confidence: 81%
“…A number of physiological studies indicate that NO can modulate pressor and reflex responses in the RVLM via an sGC/cGMP dependent mechanism [6,7,44,45]. While we were unable to detect cGMP-IR in the neurons of the C1 region, either in the resting state, when stimulated by NMDA or NO donor, or after PDE inhibition, our sGC-IR results certainly indicate the capacity for cGMP synthesis.…”
Section: Resultscontrasting
confidence: 46%
“…Work by Chan et al [19] suggests that the relative balance of functional nNOS versus inducible (i)NOS activity determines RVLM output, and further, that the different NOS isoforms activate different downstream signals, with nNOS driving sGC/cGMPdependent sympathoexcitatory responses, and NO produced by iNOS driving peroxynitrite formation and sympathoinhibitory responses [20]. Glutamate-induced pressor responses in the RVLM are in general proposed to be modulated by NO-sGC/cGMP [5,6,21] and this is supported by electrophysiological studies showing cGMPdependent potentiation of glutamate currents in RVLM slice preparations [7].…”
Section: Introductionmentioning
confidence: 62%
See 1 more Smart Citation
“…It is generally believed that different levels of NO may exert opposite effects on RVLM neurons (Chan et al, 2001) and, in turn, regulates vascular vasomotor tone via activation of different intracellular signaling pathways (Morimoto et al, 2000). In a recent study (Huang et al, 2003), we also reported an NO donor-mediated bidirectional modulation of glutamatergic transmission on RVLM neurons. Our results show that low doses of NO donors act presynaptically to elicit a reversible potentiation of synaptic transmission through NO-sensitive soluble guanosine cyclase (sGC)-cGMP signaling pathway.…”
mentioning
confidence: 75%